Performance of Islamic and conventional stock indices: empirical evidence from an emerging economy - Md Ejaz Rana; Waheed Akhter (Financial Innovation, 2015)
Background: This study aims to investigate the extent to which the conditional volatilities of both Shari'ah compliant stock and conventional stock are related to those of interest rate and exchange rate in the emerging economy of Pakistan. Methods: We used KMI 30 and KSE 100 indices for Islamic and conventional stock for the period of July 2008 to November 2013. We employed Generalized Autoregressive Conditional Heteroskedastic in the mean (GARCH-M) model. This framework relaxes constancy assumption of classical linear regression (CLRM) model and allows exchange rate and interest rate volatility to evolve over time. The GARCH-M framework also reveals results about risk-return trade-off in the context of both Islamic and conventional stock indices. Results: The findings show positive and statistically significant effect of interest rate volatility on KSE-100, whereas KMI-30 remains unaffected by the same. Exchange rate volatility is found to be significant for both conventional and Islamic indices. The relationship of risk coefficient (Ú) and stocks returns, as expected, is positive and statistically significant for both KMI-30 and KSE-100. This result is consistent with the theory of risk-return trade-off. The results of parametric t-test show significant difference between returns of both indices. This implies that Shari'ah compliant stock index (KMI-30) of Pakistan underperforms its conventional counterpart. Conclusion: By using different performance measures (Sharp ratio, Jensen alpha, Treynor ratio), this study also investigates the hypothesis that Islamic stock index has inferior performance compared with unscreened conventional counterparts due to availability of a smaller investment universe, increased monitoring costs, and limited diversification.
Keywords: 650; KMI-30; KSE-100 Index; Shari'ah; Exchange rate volatility; Interest rate volatility; Stock Performance etc